Preparation and Properties of Carboxymethyl Films from Purple Rice Flour - Anong Jainan (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The preparation and properties of carboxymethyl films from purple rice were investigated. The aims of this study were determined the optimum condition for the production of carboxymethyl flour (CMF) from purple rice, investigated the production of multifunctional film (CMFF) from CMF, thereafter, applied to use CMFF for extending crispy pork rind shelf life. Multifunctional film (CMFF) contained not only anthocyanin, but also total phenolic and total flavonoids compounds acted as a natural antioxidant. The effect of sodium hydroxide concentration (10%, 20% and 40 % w/v) on CMF properties was determined. It was found that the sodium hydroxide solution at the concentration of 10% (w / v) was the most suitable concentration for CMF synthesis. Effecting, in the degree of substitution (DS), CMF percentage, sodium chloride percentage, and the color of CMF were 0.25, 88.7, 0.91, 7.76 milligrams per 100 grams, 4.68 (ΔE), 77.08 (L *), 4.26 (a *) and 3.56 (b *), respectively. In addition, the thermal properties e.g. glass transition temperature (Tg), gelatinization temperature (Tgel) and melting temperature (Tm) were 1.19, 103.61 and 98.46 oC, respectively. In case of the CMF morphological property, the surface of flour granules was decreased with sodium concentration increased. Considering, CMF properties, the researcher was interested in CMFF production by film casting technique which combined between 2% (w/v) CMC and 1% (w/v) CMF as well as its development properties by varying the glycerol concentration i.e. 0, 0.125, 0.25, 0.5 and 1 % (w/v). Thereafter, thermal,physical, chemical and mechanical films properties were tested. The results informed that CMFF blended film at 1% (w/v) glycerol addition had the highest film water solubility was 83.56%. The elongation at break, tensile strength and water vapor permeability (WVP) were 1.66 MPa, 61.26% and 7.15 x 10-4 g⋅m/m2⋅day⋅mm⋅Hg, respectively. Furthermore, it could be report that the increase in glycerol concentration was unaffected the deterioration of anthocyanin in CMFF. The film contained anthocyanin content equal to 0.19 mg 100 g, phenolic content of 118.68 mg GAE / 100 g and total flavonoids 3.60 mg CAE / 100 g DW. Therefore, it was possible that CMFF could act as a natural antioxidant, which should be prove and evaluate its properties in term of antioxidant. In this work, the 0.25% (w/v) of glycerol was used for CMFF casting due to its properties appropriated for crispy pork rind shelf life extension; especially such as WVP and WVTR. The researcher was applied a film to extend the shelf life of crispy pork rind packing with CMFF and oriented polypropylene bags (OPP). Subsequently, the effect of fat oxidation reaction that caused to motivate rancid odor in the crispy pork rind was evaluated. After storage at room temperature, the free radical scavenging activity of antioxidant substances of CMFF was analyzed by using DPPH, ABTS and FRAPS method. It was found that the antioxidant activities were 234.78 (mg VC / 100 g), 298.32 (mg / 100 g) and 1274.25 (mg / 100 grams), respectively. The experiment showed that CMFF could extend the shelf life of crispy pork rind for 14 days without rancid odor. The physical and chemical properties of the crispy pork rind had a moisture content of 1.38 percent, the water active content was 0.44, the overall color difference was 21.75 (ΔE), 55.97, (L *), 3.03 (a *) and 17 (b *). The hardness value was 13.95 (K.gf; hardness). The crispness value and the malondialdehyde content were 73.81 (Kg.s; crispness) 0.24 (mg. / kg; malondialdehyde content), respectively.